Socialization of Modern Payment Systems: QRIS and GoPay for SME in Rempoa Urban Village, South Tangerang - Frimayasa, Agtovia; Purnama, Yanthy Herawaty; Suprayitno, Agung (Manunggal Halim Jaya, 2025)
The digital transformation of Micro, Small, and Medium Enterprises (SME) is crucial for national economic growth, particularly in adopting cashless payment systems. However, the main reason many SMEs have not yet adopted digital payment systems such as QRIS and GoPay is a lack of understanding and insufficient technical support. The aim of this Community Service Program (PKM) project is to help SME in Rempoa Village gain a better understanding and make use of modern payment technologies. The implementation method used a participatory learning approach that involved participants through lectures, discussions, application simulations, and direct use of QRIS and GoPay. The activity results showed a significant increase in participants' understanding, from 32% to 88% for QRIS and 40% to 76% in willingness to use GoPay. Participants were very interested and enthusiastic about the digitalization of business interactions. This effort demonstrated that a direct and participatory approach effectively prepares SME for the digital economy. To ensure that SME can fully and sustainably embrace digitalization, they need more support and training.